Disruption of CmHmgr1 triggers apoptosis and causes defects in growth, conidiogenesis, and mycoparasitism of Coniothyrium minitans - Xiaoxiang Yang; Haixuan Wang; Lei Zhang; Zhongmei Zhang; Zijin Hu; Daohong Jiang; Yanping Fu (Virulence, 2025)
Coniothyrium minitans is a well-known mycoparasite against Sclerotinia sclerotiorum. Two critical factors for the commercialization of C. minitans as a biocontrol agent are conidial production and parasitism. To decipher the mechanisms of conidiogenesis and mycoparasitism in C. minitans, a conidiation-deficient mutant, ZS-1TN5012, was isolated from a transfer DNA (T-DNA) insertional library. This mutant exhibited significantly reduced hyphal development, poor conidiation, and decreased sclerotial mycoparasitism. CmHmgr1 encoding a 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) was disrupted by the T-DNA insertion. The colony morphology of the wild-type strain ZS-1 resembled that of the mutant ZS-1TN5012 when the HMGR inhibitor atorvastatin was added to potato dextrose agar, with the mutant showing more sensitivity to atorvastatin. Furthermore, cellular localization assays revealed that CmHmgr1 was localized in mitochondria. Gene replacement and complementation experiments confirmed that CmHmgr1 is involved in the growth, conidiogenesis and mycoparasitism of C. minitans, and disruption of CmHmgr1 triggers apoptosis.